An analysis of racial stereotyping of the South African Police in the television programmes Carte Blanche and Special Assignment from August 2003 to September 2004 - Gerbi, Giovanna Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2005.